2020
DOI: 10.1177/1024907919857666
|View full text |Cite
|
Sign up to set email alerts
|

E‐learning in advanced cardiac life support: Outcome and attitude among healthcare professionals

Abstract: Background: Advanced cardiac life support provides healthcare professionals with knowledge and skills needed in dealing with cardiac emergencies. By incorporating e-learning in advanced cardiac life support courses, it allows for easier accessibility of learning materials and a more personalized learning schedule at a lower overall cost. Objectives: This study aims to compare the outcome of e-learning advanced cardiac life support versus conventional advanced cardiac life support among healthcare professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…For the important outcome of knowledge at course conclusion, we also found very low-certainty evidence (downgraded for risk of bias and imprecision) reported by 1 RCT 254 and 2 non-RCTs. 255,256 The RCT, randomizing 3732 participants of ALS courses to either 6 to 8 hours of eLearning plus 1 day of face-to-face training or to a traditional 2-day ALS course, 254 reported no statistical difference for end-of-course MCQ test scores (I: 88.96% versus C: 89.54%; adjusted difference, 0.55%; CI, À1.11% to 0.02%; P = 0.054). The first non-RCT, with 96 ACLS course participants 255 comparing 6 hours of online lectures plus a 1-day face-to-face course with a traditional 2day face-to-face course, showed that MCQ pass rates at course conclusion did not differ statistically (C: 85.4% versus I: 95.8%; P = 0.08).…”
Section: Consensus On Sciencementioning
confidence: 99%
See 4 more Smart Citations
“…For the important outcome of knowledge at course conclusion, we also found very low-certainty evidence (downgraded for risk of bias and imprecision) reported by 1 RCT 254 and 2 non-RCTs. 255,256 The RCT, randomizing 3732 participants of ALS courses to either 6 to 8 hours of eLearning plus 1 day of face-to-face training or to a traditional 2-day ALS course, 254 reported no statistical difference for end-of-course MCQ test scores (I: 88.96% versus C: 89.54%; adjusted difference, 0.55%; CI, À1.11% to 0.02%; P = 0.054). The first non-RCT, with 96 ACLS course participants 255 comparing 6 hours of online lectures plus a 1-day face-to-face course with a traditional 2day face-to-face course, showed that MCQ pass rates at course conclusion did not differ statistically (C: 85.4% versus I: 95.8%; P = 0.08).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…255,256 The RCT, randomizing 3732 participants of ALS courses to either 6 to 8 hours of eLearning plus 1 day of face-to-face training or to a traditional 2-day ALS course, 254 reported no statistical difference for end-of-course MCQ test scores (I: 88.96% versus C: 89.54%; adjusted difference, 0.55%; CI, À1.11% to 0.02%; P = 0.054). The first non-RCT, with 96 ACLS course participants 255 comparing 6 hours of online lectures plus a 1-day face-to-face course with a traditional 2day face-to-face course, showed that MCQ pass rates at course conclusion did not differ statistically (C: 85.4% versus I: 95.8%; P = 0.08). The second study, including 27170 participants of ALS courses, 256 compared 6 to 8 hours of eLearning plus 1 day of face-toface training with a traditional 2-day face-to-face ALS training.…”
Section: Consensus On Sciencementioning
confidence: 99%
See 3 more Smart Citations